The Role of Circulating T Follicular Helper Cells and Regulatory Cells in Non‐Small Cell Lung Cancer Patients. (August 2017) - Guo, Z.; Liang, H.; Xu, Y.; Liu, L.; Ren, X.; Zhang, S.; Wei, S.; Xu, P.
Abstract: T follicular helper (Tfh) cells and T follicular regulatory (Tfr) cells are identified as the new subset of immune cells. This study aims to investigate the role of circulating Tfh cells (cTfh) and Tfr (cTfr) cells in the pathogenesis of non‐small cell lung cancer (NSCLC). A total of 27 NSCLC patients and 19 age and sex‐matched healthy controls were enrolled. The percentage of cTfh and cTfr was detected by flow cytometric analysis. Compared to healthy controls, a significantly higher percentage of both cTfh and cTfr cells were observed in NSCLC patients (for cTfh, 18.88% ± 16.84% versus 5.98% ± 3.70%, P  <   0.01; for cTfr, 2.67% ± 2.20% versus 1.14% ± 0.76%, P  <   0.01). Furthermore, there was a positive correlation between cTfh/cTfr ratio and age in NSCLC patients ( P  <   0.05). When taking age 60 as a cut‐off, the percentage of both cTfh cells and cTfr cells were higher in older patients than younger patients. Moreover, our data showed there was lower percentage of cTfh cells in NSCLC patients with early stage disease (I and II) (12.10% ± 12.22%) than that in advanced stage disease (III and IV) (30.41% ± 17.87%) ( P  <   0.01). However, no significant relationship was observed between cTfr cells and clinical stage in NSCLC patients. A higher percentage of cTfh cells was observed in patients with squamous cell carcinoma compared with adenocarcinoma (31.70% ± 20.73% versus. 13.48% ± 11.78%, P  <   0.05). Taken together, there was significantly higher percentage of cTfh and cTfr cells in NSCLC patients. cTfh and cTfr cells might play an important role in the pathogenesis of NSCLC patients.